Disentangling responses to natural stressor and human impact gradients in river ecosystems across Europe. Issue 2 (27th November 2021) - Stubbington, Rachel; Sarremejane, Romain; Laini, Alex; Cid, Núria; Csabai, Zoltán; England, Judy; Munné, Antoni; Aspin, Thomas; Bonada, Núria; Bruno, Daniel; Cauvy‐Fraunie, Sophie; Chadd, Richard; et al.
Abstract: Rivers are dynamic ecosystems in which both human impacts and climate‐driven drying events are increasingly common. These anthropogenic and natural stressors interact to influence the biodiversity and functioning of river ecosystems. Disentangling ecological responses to these interacting stressors is necessary to guide management actions that support ecosystems adapting to global change. We analysed the independent and interactive effects of human impacts and natural drying on aquatic invertebrate communities—a key biotic group used to assess the health of European freshwaters. We calculated biological response metrics representing communities from 406 rivers in eight European countries: taxonomic richness, functional richness and redundancy, and biomonitoring indices that indicate ecological status. We analysed metrics based on the whole community and a group of taxa with traits promoting resistance and/or resilience ('high RR') to drying. We also examined how responses vary across Europe in relation to climatic aridity. Most community metrics decreased independently in response to impacts and drying. A richness‐independent biomonitoring index (the average score per taxon; ASPT) showed particular potential for use in biomonitoring, and should be considered alongside new metrics representing high RR diversity, to promote accurate assessment of ecological status. High RR taxonomic richness responded only to impacts, not drying. However, these predictors explained little variance in richness and other high RR metrics, potentially due to low taxonomic richness. Metric responsiveness could thus be enhanced by developing region‐specific high RR groups comprising sufficient taxa with sufficiently variable impact sensitivities to indicate ecological status. Synthesis and applications . Metrics are needed to assess the ecological status of dynamic river ecosystems—including those that sometimes dry—and thus to identify priority sites requiring action to tackle the causes of environmental degradation. Our results inform recommendations guiding the development of such metrics. We propose concurrent use of richness‐independent 'average score per taxon' indices and metrics that characterize the richness of resistant and resilient taxa. We observed interactions between aridity, impacts and drying, highlighting that these new metrics should be region specific, river type specific and adaptable, promoting their ability to inform management actions that protect biodiversity in river ecosystems responding to climate change. Abstract : Metrics are needed to assess the ecological status of dynamic river ecosystems—including those that sometimes dry—and thus to identify priority sites requiring action to tackle the causes of environmental degradation. Our results inform recommendations guiding the development of such metrics. We propose concurrent use of richness‐independent 'average score per taxon' indices and metrics that characterize the richness of resistant and resilient taxa. We observed interactions between aridity, impacts and drying, highlighting that these new metrics should be region specific, river type specific and adaptable, promoting their ability to inform management actions that protect biodiversity in river ecosystems responding to climate change. Resum: Els rius són ecosistemes dinàmics subjectes a impactes humans i fenòmens naturals de sequera, cada vegada més comuns. Aquestes pertorbacions antròpiques i naturals interactuen i en determinen la biodiversitat i el funcionament dels ecosistemes fluvials. Entendre millor les respostes ecològiques a aquests dos tipus de pertorbacions és necessari per guiar accions de gestió de cara a l'adaptació al canvi global. Hem analitzat els efectes independents i interactius dels impactes humans i de la sequera sobre les comunitats d'invertebrats aquàtics, un grup d'organismes clau per avaluar l'estat ecològic dels ecosistemes d'aigua dolça europeus. Hem calculat mètriques biològiques usant comunitats de 406 rius de vuit països europeus: riquesa taxonòmica, riquesa funcional i redundància, i dos índexs biològics usats en l'avaluació de l'estat ecològic. Hem analitzat mètriques basades en tota la comunitat, i un grup de tàxons amb trets característics que afavoreixen la resistència i/o la resistència ('RR elevat') a la sequera. També hem examinat com les respostes varien a tot Europa en relació amb l'aridesa del clima. La majoria de les mètriques basades en tota la comunitat biològica van disminuir de manera independent als impactes i a la sequera. Un índex biològic que és independent de la riquesa taxonòmica (la puntuació mitjana per tàxon; ASPT) va mostrar una bona resposta per ser usat en biomonitoratge, i s'hauria de considerar, juntament amb les noves mètriques que representen una alta diversitat de RR, per promoure una avaluació precisa de l'estat ecològic. L'alta riquesa taxonòmica de RR només va respondre als impactes, no a la sequera. No obstant això, aquests predictors van explicar poca variació en la riquesa i altres mètriques basades amb elevats valors RR, potencialment a causa de la baixa riquesa taxonòmica. Per tant, aquestes mètriques es podrien millorar mitjançant el desenvolupament de mètriques amb valors RR elevats específics de la regió, que incloguin suficients tàxons prou sensibles per indicar l'estat ecològic. Síntesi i aplicacions . Es necessiten mètriques per avaluar l'estat ecològic dels ecosistemes fluvials dinàmics, inclosos els que de vegades s'assequen, i així identificar els llocs prioritaris on identificar i afrontar les causes de la degradació del medi. Els nostres resultats proporcionen recomanacions que guien el desenvolupament d'aquestes mètriques. Recomanem la consideració simultània d'índexs i mètriques 'puntuació mitjana per taxó' independents de la riquesa, que caracteritzen la riquesa de tàxons resistents i resistents. Les interaccions observades entre aridesa, impactes i la sequera ressalten que aquestes noves mètriques haurien de ser específiques per a la regió, específiques per tipus i adaptables, promovent la seva capacitat d'informar les accions de gestió que protegeixin la biodiversitat dels ecosistemes fluvials, i que responguin al canvi climàtic.